Learning geospatial analysis with Python : understand GIS processing tasks and remote sensing data analysis using Python 3.7 - Lawhead, Joel (Packt Publishing, 2019)
Geospatial Analysis is used in almost every field you can think of from medicine to defense, to farming. Learning Geospatial Analysis with Python, Third Edition would be a helpful guide to Geographic Information Systems and Remote Sensing Analysis using Python 3.7 without overwhelming the reader.